Bright Blue, Green, and Red Luminescence from Dye-Sensitized Core@Shell Upconversion Nanophosphors under 800 nm Near-Infrared Light - Hong, A-Ra; Han, Joon Soo; Kang, Gumin; Ko, Hyungduk; Jang, Ho Seong (MDPI, 2020)
In this study, Li-based blue- and green-emitting core@shell (C@S) upconversion nanophosphors (UCNPs) and NaGdF4-based red-emitting C@S UCNPs were synthesized, and IR-808 dyes were conjugated with the C@S UCNPs to enhance upconversion (UC) luminescence. The surface of the as-synthesized C@S UCNPs, which was originally capped with oleic acid, was modified with BF4- to conjugate the IR-808 dye having a carboxyl functional group to the surface of the UCNPs. After the conjugation with IR-808 dyes, absorbance of the UCNPs was significantly increased. As a result, dye-sensitized blue (B)-, green (G)-, and red (R)-emitting UCNPs exhibited 87-fold, 10.8-fold, and 110-fold enhanced UC luminescence compared with B-, G-, and R-emitting Nd3+-doped C@S UCNPs under 800 nm near-infrared (NIR) light excitation, respectively. Consequently, dye-sensitized UCNPs exhibiting strong UC luminescence under 800 nm NIR light excitation have high applicability in a variety of biological applications.